(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The purpose of this study is to examine and characterize students’ use of deductive reasoning when addressing mathematical problems using linear programming that is based on the Adversity Quotient. This kind of study is qualitative and descriptive. Purposive sampling was the method of sampling employed in this study. There were three different sorts of pupils in class XI IPA I SMA Negeri 5 Batanghari: Quitter, Camper, and Climber types. There were 19 total participants in the study. Each category was represented by one subject, resulting in three students who were chosen as research subjects. Questionnaires, interviews, and tests of problem-solving were the research instruments employed in this study. The processes of (1) Reducing the data, (2) Presenting the data, and (3) Concluding were used to evaluate the collected data. The research’s findings demonstrate that Quitter-type kids are capable of performing calculations based on rules or formulas to comprehend difficulties. Still, they are unable to meet the problem-solving markers when it comes to formulating logical conclusions and gathering direct evidence. Students who are camper type can compute using rules or formulas to comprehend problems, plan, and carry out plans, but they are unable to double-check. Students cannot meet the issue-solving markers when they are gathering direct facts and generating logical conclusions. Students who are climber types can satisfy deductive reasoning requirements by comprehending problems, making plans, carrying them out, and double-checking.